Teachers Pedagodical And Subject Matter Competence For Effective Instructional Delivery Of Pre-Vocational Studies Curriculum In Upper Basic Education In South East Nigeria - Onwadi, Rachael; Obasi, Susan (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2025)
It is indisputable that teachers have an impact on how well school courses are taught. In a similar vein, teachers' ability to effectively teach subjects is crucial to students' academic success. This study evaluated the pedagogical and subject-matter proficiency of teachers in upper basic education in southeast Nigeria for the purpose of effectively delivering the pre-vocational studies curriculum. Two research questions and two related hypotheses were developed in order to accomplish the study's goal. The descriptive survey design was used in the investigation. In 1,305 upper basic schools across the five states of southeast Nigeria, there were 2,610 management staff members and 1,865 pre-vocational teachers who comprised the study's population. The stratified and simple random sampling method was used to select 232 managements and 332 prevocational subject teachers as the study's sample size. A reliability index of 0.91 was determined. Frequency counts and mean scores for the study questions were utilized to descriptively examine the data, and the t-test and ANOVA were employed to assess the hypotheses. According to a one-way ANOVA, the mean effects of teachers' subject matter expertise on the implementation of the pre-vocational studies curriculum in upper basic education across the five states of southeast Nigeria were statistically negligible. An action plan should be implemented by the government and management to increase teachers' proficiency in using contemporary pedagogy for the successful implementation of pre-vocational curricula. To support teachers' professional development and efficacy in teaching pre-vocational studies, it is important to encourage ongoing supervision of instruction.